Analysis of Factors Affecting Subjective Well-Being of the Couple Adopting a Child in Darul Imarah Sub-District of Aceh Besar Regency in 2021 - Junizar Junizar; Rika Dewi (Universitas Serambi Mekkah, 2022)
For Acehnese, having children is a dream of every family. Therefore, if a couple who has been married for more than two years has not had children, conflicts often occur in the family. Generally, wives are blamed as the main cause of having no children even though that is not necessarily true. Moreover, in Aceh, husbands are often embarrassed to see a doctor since they have fear of knowing the real cause of having no children. This condition has turned out to be a parameter of a person's success in a marriage and even causes conflicts that might result in a divorce. This study aimed to examine various factors that affect the subjective well-being of a married couple adopting a child in Darul Imarah Sub-district of Aceh Besar Regency. A qualitative design was employed in this research. The respondents were a married couple and an informant as a source of triangulation of information. Those respondents were chosen by using a purposive sampling technique. The research data were collected in July 2021 through interviews and observations, and the data analysis was carried out using data reduction, data display, and verification. The results showed that the couple has adopted a child, and they have been happy. They have always understood each other's strengths and weaknesses, actively communicated, supported each other, and made decisions according to mutual needs, so their subjective wellbeing has been stable. Two factors affecting the subjective well-being in this couple were internal factors including their optimism, self-esteem, and religious values, and external factors including wife's health regarding having undergone cyst surgery, the wife's age of 40, and support from a big family. Keywords: subjective well-being, married couples, offspring.